Environmental geology - Reichard, James S. (McGraw-Hill, 2011)
Reichard's Environmental Geology emphasizes human interaction with the environment within a geological context. The writing style holds the interest of nonmajor students, and the text brings applications to the forefront so that students feel a connection to the topic.